Continuous multiparametric monitoring of cell metabolism in response to transient overexpression of the sirtuin deacetylase SIRT3 - Dransfeld, Christian-Lars; Alborzinia, Hamed; Wölfl, Stefan; Mahlknecht, Ulrich (Clinical epigenetics, 2010)
The analysis and visualisation of research data in an environment which is most similar to living conditions belong to the most challenging claims of present scientific research endeavours. To date, the effect of protein function on cell metabolism is most commonly assessed from a series of end point analyses, which finally allows an approximate estimation on how a specific effect takes its course. In the study presented herein, we demonstrate how the combination of transient transfection and a biosensor chip system gives the opportunity to analyse the effect of a specific protein on cell metabolism in living cells through real-time monitoring of metabolically relevant parameters, such as oxygen consumption, acidification rate and cell adhesion. In addition, this method allows online monitoring of the time course of metabolic changes due to changes in expression levels of metabolic regulative proteins from the time of transfection to maximum overexpression. The methodology presented herein was assessed for the transient overexpression of the sirtuin deacetylase SIRT3, a mitochondrial key element in the regulation of energy metabolism, metabolic disease, cancer and ageing.